Perceived attributes of internet - based interorganizational systems: a research in Greek firms - Gitsalis, Nikolaos (SPOUDAI Journal of Economics and Business, 2009)
InterOrganizational Systems are technology solutions that facilitate corporate buying using the Internet. As previous research has shown that buyers' usage of InterOrganizational Systems is influenced by the perceived risks and expected benefits associated with such systems, the main objective in this paper is to investigate whether these benefits and risks are differentiated between users and non users of InterOrganizational Systems or not. Data for the study were gathered through a survey of Greek firms, using a questionnaire. The results suggest that although there was no differentiation between users and non users for the majority of perceived benefits, in the case of perceived risks there are more differences between users and non users. JEL Classifications: C42, O31, O33